Developing higher level thinking skills - Villamin, Araceli M. (2002)
The pervasiveness of language in the teaching of all subjects and the close ties of oral and written language to thinking suggest that language across the curriculum is a primary concept in developing all thinking skills.
Keywords: Critical thinking; Thought and thinking; Cognitive ability